The Cost-Effectiveness of Intermittent Preventive Treatment for Malaria in Infants in Sub-Saharan Africa - Conteh, Lesong (Public Library of Science, 2010)
BACKGROUND: Intermittent preventive treatment in infants (IPTi) has been shown to decrease clinical malaria by approximately 30% in the first year of life and is a promising malaria control strategy for Sub-Saharan Africa which can be delivered alongside the Expanded Programme on Immunisation (EPI). To date, there have been limited data on the cost-effectiveness of this strategy using sulfadoxine pyrimethamine (SP) and no published data on cost-effectiveness using other antimalarials. METHODS: We analysed data from 5 countries in sub-Saharan Africa using a total of 5 different IPTi drug regimens; SP, mefloquine (MQ), 3 days of chlorproguanil-dapsone (CD), SP plus 3 days of artesunate (SP-AS3) and 3 days of amodiaquine-artesunate (AQ3-AS3).The cost per malaria episode averted and cost per Disability-Adjusted Life-Year (DALY) averted were modeled using both trial specific protective efficacy (PE) for all IPTi drugs and a pooled PE for IPTi with SP, malaria incidence, an estimated malaria case fatality rate of 1.57%, IPTi delivery costs and country specific provider and household malaria treatment costs. FINDINGS: In sites where IPTi had a significant effect on reducing malaria, the cost per episode averted for IPTi-SP was very low, USD 1.36–4.03 based on trial specific data and USD 0.68–2.27 based on the pooled analysis. For IPTi using alternative antimalarials, the lowest cost per case averted was for AQ3-AS3 in western Kenya (USD 4.62) and the highest was for MQ in Korowge, Tanzania (USD 18.56). Where efficacious, based only on intervention costs, IPTi was shown to be cost effective in all the sites and highly cost-effective in all but one of the sites, ranging from USD 2.90 (Ifakara, Tanzania with SP) to USD 39.63 (Korogwe, Tanzania with MQ) per DALY averted. In addition, IPTi reduced health system costs and showed significant savings to households from malaria cases averted. A threshold analysis showed that there is room for the IPTi-efficacy to fall and still remain highly cost effective in all sites where IPTi had a statistically significant effect on clinical malaria. CONCLUSIONS: IPTi delivered alongside the EPI is a highly cost effective intervention against clinical malaria with a range of drugs in a range of malaria transmission settings. Where IPTi did not have a statistically significant impact on malaria, generally in low transmission sites, it was not cost effective.